Examining the mediating role of moral intelligence in the relationship between general intelligence and marital satisfaction in married women - Rafaei, Tara; Mehrpour, Mohammadhossein; Liaghat, Ehsan; Ranjbar, Behrad; Namjoo, Farhad (Psychology of Woman Journal, 2020)
The purpose of the current research was to explain the relationship between the dimensions of general intelligence and marital satisfaction with the mediating role of moral intelligence. The current research was descriptive and correlational. The statistical population of the research was made up of all married women of Yasouj city in 2020. Among the statistical population, 150 married women were selected and studied as available sampling. To collect data, Cattell's general intelligence, Lennick's and Keil's moral intelligence and Enrich's marital satisfaction questionnaires were used. After collecting and extracting the data, the scores of the participants were analyzed using hierarchical regression analysis. The results of the hierarchical regression analysis showed that moral intelligence has a significant mediating role in relation to the dimensions of general intelligence and marital satisfaction in married women. According to these findings, it can be concluded that when a person has used the function of his intelligence to internalize moral values, he can have richer reasoning and benefit from higher marital satisfaction.